2017
DOI: 10.1002/bies.201700018
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome‐Germline Interactions and Their Transgenerational Implications

Abstract: It is becoming increasingly clear that most, if not all, animals and plants are associated with a diverse array of resident gut microbiota. This symbiosis is regulated by host-microbiome interactions which influence the development, homeostasis, adaptation and evolution of the host. Recent evidence indicated that these interactions can also affect the host germline and have a potential of supporting transgenerational effects, including inheritance of acquired characteristics. Taken together, the influence of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 104 publications
(172 reference statements)
1
5
0
Order By: Relevance
“…The contribution of acquired microbiota in offspring transcriptional responses seems consistent with previous studies showing an influence of gut microbiota on thermal phenotype and a correlation of gut microbiome load with cold tolerance in D. melanogaster as well as an association between the gut microbiota composition and host physiology in cold tolerance in the field cricket Gryllus veletis . Indeed, emerging evidence increasingly support, across species, microbiome–germline interaction and bacteria‐mediated transgenerational inheritance .…”
Section: Resultssupporting
confidence: 87%
“…The contribution of acquired microbiota in offspring transcriptional responses seems consistent with previous studies showing an influence of gut microbiota on thermal phenotype and a correlation of gut microbiome load with cold tolerance in D. melanogaster as well as an association between the gut microbiota composition and host physiology in cold tolerance in the field cricket Gryllus veletis . Indeed, emerging evidence increasingly support, across species, microbiome–germline interaction and bacteria‐mediated transgenerational inheritance .…”
Section: Resultssupporting
confidence: 87%
“…Gut microbiota has also been shown to impact germline function and reproduction (Elgart and Soen, 2018;Elgart et al, 2016;Fridmann-Sirkis et al, 2014;Henriques et al, 2020;Morimoto et al, 2017;Nguyen et al, 2020). Removal of gut microbiota in D. melanogaster repressed oogenesis in germ-free (GF) females (Elgart et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…[141] Moreover, the rapid adaptation of the microbiome to stress (exposure to a toxic agent) and selection of resistant bacteria may enable the host's offspring to develop higher toxic tolerance, [142,143] which could be inherited though different channels of microbial transmission. [143,144] Finally, microbiome-driven adaptations to new diets may explain the consumption of seaweed in humans, [145] the evolution of herbivory in cows, [146] and sanguivory in vampire bats. [147] For example, it has been suggested that a substantial part of the morphological, immunological, and physiological adaptations necessary to cope with the new diet of vampire bats were not due to genomic adaptations in the host, but rather were driven by positive selection on genes in the functional core microbiome of com-…”
Section: Re-establishing the Host-microbiome Equilibriummentioning
confidence: 99%